TANGGUNG JAWAB PEMERINTAH SEBAGAI AKIBAT PENGARUH ASAP KEBAKARAN LAHAN DAN HUTAN DI PROVINSI RIAU BERDASARKAN UNDANG-UNDANG NOMOR 36 TAHUN 2009 TENTANG KESEHATAN - Muhammad Zaqi Reyhan; Ardiansyah Ardiansyah; Aliar Syam (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2021)
The form of responsibility that has not been realized by the government is that there are still forest and land fires that cause poor health, so it is necessary to take firm action from the government to immediately realize the compensation for the impact of the smoke. In the end everyone, women, young people, children have the right to other fundamental health related and highly dependent on a healthy environment. The formulation of the problem in this study is the responsibility of the government as a result of the effects of the smoke from land and forest fires in Riau Province based on Law Number 36 of 2009 concerning Health, due to the legal responsibility of the government as a result the effect of smoke from land and forest fires in Riau Province based on Law Number 36 of 2009 concerning Health. The method used is normative legal research. Sources of data consist of primary legal materials, secondary legal materials, and tertiary legal materials. In this study the data were analyzed qualitatively and in drawing conclusions, the authors applied the deductive thinking method. The conclusion in this study has answered the problems that arise, namely the responsibility of the government as a result of the influence of the smoke from land and forest fires in Riau Province based on Law Number 36 of 2009 concerning Health, that the state's responsibility to fulfill the right to health has at least 3 forms, namely respecting the right to health, protecting the right to health and fulfilling the right to health. The government should uphold the right to health for all people in order to improve a healthy standard of living in order to realize the highest public health standard, and this is also the responsibility of the state for the realization of fundamental rights in the health sector. The conception of state responsibility in fulfilling the right to health is a positive legal right, therefore the government is obliged as the personification of the state to fulfill the rights of citizens' health. The neglect of the right to public health in the form of denial of the protection and provision of proper public health services is a violation of the constitution. The legal consequence is the government's responsibility as a result of the influence of the smoke from land and forest fires in Riau Province based on Law Number 36 of 2009 concerning Health that health is fundamental rights of every human being, therefore every individual, family and society has the right to receive protection for their health. The government is responsible for regulating and protecting the right to optimal public health. The government's responsibility in fulfilling the right to health is manifested in the provision of proper health facilities and facilities that are easily accessible to the public.